Barth backwards: reading the Church Dogmatics 'from the end'. Issue 4 (6th December 2018) - McDonald, Rob
Abstract: This article proposes a way of reading Karl Barth's Church Dogmatics backwards or 'from the end'. Employing this method to explore The Doctrine of God and The Doctrine of the Word of God highlights two aspects of Barth's theology. The first is the importance of communion to Barth's account of the immanence and economy of God, especially in his understanding of God as the 'Lord of Glory'. The second is Barth's careful balancing of christology and pneumatology across the first two volumes of the Dogmatics through the use of a chiastic structure that underpins his construal of divine election and his account of divine revelation.